Life Course Prevalence of Bullying among University Students in Mainland China: A Multi-university Study. Issue 7 (April 2022) - Su, Pu-Yu; Wang, Geng-Fu; Xie, Guo-Die; Chen, Li-Ru; Chen, Shan-Shan; He, Yang
Little is known about the life course prevalence of bullying among university students. The current study examined the prevalence of bullying in different life periods among multi-university students. Our study included 4, 034 university students from four types of universities. Participants self-reported four types of bullying (i.e., physical, verbal, relational, and cyber) with bullies and victims, and four periods (i.e., primary school or earlier, middle school, high school, and postsecondary education). Overall, the percentage of university students experiencing at least one type of bullying victimization (BV) and bullying perpetration (BP) during their lifetime was 59.7% and 31.6%, respectively; the percentage of the university students experiencing more than two types of BV and BP was 16.3% and 7.4%, respectively. The prevalence rates of each type of BV and BP were the highest in elementary school or earlier, and these rates decreased from elementary school or earlier to postsecondary education period. Four latent classes were identified for BV: low BV (73.8%), moderate BV (18.6%), secondary school BV (4.4%), and persistent BV (3.2%). Similarly, four classes for BP were identified: low BP (86.6%), primary school BP (8.1%), high school BP (1.5%), and persistent BP (3.8%). These findings may inform school health practice of bullying prevention by taking prevention programs, especially during elementary school or earlier period.